Pemahaman Matematis Siswa SMP Dalam Menyelesaikan Masalah Kubus dan Balok Ditinjau Dari Tipe Kepribadian Keirsey: Middle School Students' Mathematical Understanding in Solving Cube and Block Problems Judging from Keirsey's Personality Type - Indraswari, Nur; Kaila, Ufil (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Nahdlatul Ulama Kalimantan Selatan, 2024)
Research is a type of exploratory research with a qualitative descriptive approach. The goal is to describe the mathematical understanding of junior high school students in solving flat-sided geometrical problems in terms of Keirsey's personality type. The research subjects were 4 grade VIII students of SMPN 1 Bluto who were of the same gender, had equal abilities, representing 4 keirsey personality types. Three indicators to reveal mathematical understanding are Translation and Interpretation, Extrapolation, and Application. On the Translation and Interpretation indicator, it was found that students were able to classify known and asked objects in problems. The four subjects can identify things that are known and asked based on what they observe and understand, determine the concept of completion obtained from the size of a unit cube. Counting the colored and uncolored sides using addition and subtraction operations to obtain the ratio of the number of colored and uncolored sides of the cube. Based on the SA,SR,SI Translation and Interpretation Indicators visualize with pictures. SG states the number of sides of the entire cube. Extrapolation indicators, SA, SI use the concept of the volume formula and SR, SG uses logic or reasoning, SR, SI uses symbols to express the colored and non-colored sides. The SI Application Indicator has a writing error in the calculation of the operation. In SG, there was an misunderstanding of the intent of the question in determining the initial settlement so that it affected the results.